1999
DOI: 10.1073/pnas.96.5.2065
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppression in human skin carcinoma cells by chromosome 15 transfer or thrombospondin-1 overexpression through halted tumor vascularization

Abstract: The development of skin carcinomas presently is believed to be correlated with mutations in the p53 tumor suppressor and ras gene as well as with the loss of chromosome 9. We now demonstrate that, in addition, loss of chromosome 15 may be a relevant genetic defect. Reintroduction of an extra copy of chromosome 15, but not chromosome 4, into the human skin carcinoma SCL-I cells, lacking one copy of each chromosome, resulted in tumor suppression after s.c. injection in mice. Transfection with thrombospondin-1 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 41 publications
(50 reference statements)
3
78
0
3
Order By: Relevance
“…One exception may be loss of chromosome 15, the only common aberration. We previously showed that loss of chromosome 15 correlated with loss of the angiogenesis inhibitor TSP-1 which in turn correlated with the angiogenic switch required for malignant conversion (Folkman and Hanahan, 1991;Bleuel et al, 1999). We recently also showed that loss of chromosome 15 occurs in human skin carcinomas and that this correlated with progression from benign to malignant tumor phenotype (Burnworth et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…One exception may be loss of chromosome 15, the only common aberration. We previously showed that loss of chromosome 15 correlated with loss of the angiogenesis inhibitor TSP-1 which in turn correlated with the angiogenic switch required for malignant conversion (Folkman and Hanahan, 1991;Bleuel et al, 1999). We recently also showed that loss of chromosome 15 occurs in human skin carcinomas and that this correlated with progression from benign to malignant tumor phenotype (Burnworth et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…epithelial membrane protein 1 (Emp1), Dusp4 and cyclin D) are proteins associated with proliferation and tumorigenesis (Bartkova et al, 1994;Hippo et al, 2001;Wang et al, 2003;Wang et al, 1994). Correspondingly, antiproliferative genes such as Btg2 and genes with tumor suppressor functions such as Fibroblast growth factor 2 (FGFR2) (Eswarakumar et al, 2005) and Thrombospondin-1 (TSP-1) (Bleuel et al, 1999;Castle et al, 1997) were down regulated in response to FGF-8b (Supplemental table 2 is a large glycoprotein secreted by various cell types. In normal mammalian tissue TSP-1 is a natural occurring angiogenic inhibitor which helps to maintain the normal quiescent vasculature (Bouck et al, 1996;Good et al, 1990;Hanahan and Folkman, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In normal mammalian tissue TSP-1 is a natural occurring angiogenic inhibitor which helps to maintain the normal quiescent vasculature (Bouck et al, 1996;Good et al, 1990;Hanahan and Folkman, 1996). Because of its antiangiogenic properties, overexpression of TSP-1 slows tumor growth in various experimental mouse models including breast cancer (Bleuel et al, 1999;Castle et al, 1997;Weinstat-Saslow et al, 1994;Volpert et al, 1998). Suppression of TSP-1 mRNA and protein in response to FGF-8b in breast cancer cells has also been shown in a previous study by our group (Mattila et al, 2006) which strengthens the finding of this study.…”
Section: Discussionmentioning
confidence: 99%
“…HaCaT cells were routinely cultured as described (Boukamp et al, 1988) and tumor formation was analysed as previously described (Bleuel et al, 1999). To recultivate cells from nude mouse tumors, these were excised, quickly rinsed in 70% ethanol, thoroughly washed in MEM culture medium and minced.…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%